PERBEDAAN MAKNA TERJEMAHAN AL-QURAN DALAM BAHASA INDONESIA DAN MALAYSIA DAN PENGARUHNYA TERHADAP PERILAKU MASYARAKAT - Ikhda Rahmatina; Rika Astari (Universitas Ahmad Dahlan, 2020)
The purpose of this study is to describe the difference meaning in Quranic translation in Bahasa and Malay version and its influence in people's behaviour. The population of this research is the Muslim college students comunity in Indonesia and Malaysia who understand Arabic. The respondent is choosen by simple purpose of sampling and those are 28 students from University Ahmad Dahlan, Indonesia, Universiti Malaya and Univeristi Teknologi MARA, Malaysia. The data were generated using qualitative descriptive research instrument, such as documentaries studies, questionnaires, and interviews. The data were analyzed using speaking and listening method and recording and coding method. The findings show that the differences in translation of word auliya' in QS Al-Maidah 51 affect people's behaviour in choosing the political leader, in both of Indonesia and Malaysia. Meanwhile, the differences in translation of word khiftum in QS an-Nisa' 3 affects and is affected Indonesian and Malaysian's culture in polygamy practice.